Vietnam : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper assesses the impact of Vietnam's World Trade Organization (WTO) accession. It describes the main terms of Vietnam's accession as regards trade in goods and services, and uses a partial equilibrium simulation model to estimate the likely impact of WTO accession on revenues and consumer welfare. The paper provides a more general overview of the effects of WTO accession for Vietnam and its main trading partners. It also reviews the main causes of the recent stock market developments and policy measures taken thus far and discusses challenges ahead.